Security communication and energy efficiency optimization strategy in UAV-aided edge computing - Xueyong YU; Lixiang QIU; Jianing SONG; Hongbo ZHU (Tongxin xuebao)
The flexible mobility of the unmanned aerial vehicle (UAV) has attracted widespread attention in the mobile edge computing (MEC) system.However, the existence of eavesdroppers in the air makes it a huge challenge for its secure transmission.In order to solve the contradiction between high safe communication rate and low energy consumption, the concept of security communication energy efficiency was introduced, that was, the ratio between UAV safe communication transmission rate and UAV energy consumption.Firstly, to subject the task delay constraint, limited UAV CPU frequency and task offloading rate constraint, an offloading strategy was proposed to maximize the energy efficiency of secure communication by jointly optimizing the legal UAV hover location, CPU frequency allocation and distinguishing the complexity of computing tasks, while improving the security communication in the UAV-MEC scenario from the perspective of physical layer security.Secondly, to address the non-convex optimization problem, it was decomposed into three sub-problems that were solved with block coordinate descent and the successive convex approximation (SCA) methods respectively.The simulation results show that, with different task complexity, the proposed strategy can balance the relationship between the overall secure communication performance and energy consumption, while meeting the offloading requirements of ground terminals.And then it improves secrecy energy efficiency.